A framework for guiding learning in ultrasound scanning. (February 2015) - Crofts, Gillian
Ultrasound scanning is provided by a range of health professionals who need to be trained to a proficient level. In respect of education and training in ultrasound scanning, little attention has been given to how scanning skills are acquired and what assists and hinders the learning process. This study aims to develop a framework for guiding learning in ultrasound scanning. Overt participant observation and semi-structured interviews generated data on four learners undertaking a 12-month postgraduate ultrasound programme. Narrative analysis of the interview data was used to reveal dominant themes related to stages in learning to scan. Dominant themes associated with learning to scan were communication with the patient, navigation skills, image interpretation skills, observation of expert practice, feedback on performance and random practise. Detailed interpretation of the themes through narrative analysis provided characteristics of learning for each stage of a four staged process. This study provides an insight into the key features of scan performance and how scanning skills are acquired over a four-staged approach. These themes and characteristics are presented in a framework for guiding learning in ultrasound scanning.